Effect of solvation on the vertical ionization energy of thymine: from microhydration to bulk - Ghosh, Debashree; Isayev, Olexandr; Slipchenko, Lyudmila V.; Krylov, Anna I. (Journal of Physical Chemistry A, 2011)
The effect of hydration on the vertical ionization energy (VIE) of thymine was characterized using equation-of-motion ionization potential coupled-cluster (EOM-IP-CCSD) and effective fragment potential (EFP) methods. We considered several microsolvated clusters as well as thymine solvated in bulk water. The VIE in bulk water was computed by averaging over solvent-solute configurations obtained from equilibrium molecular dynamics trajectories at 300 K. The effect of microsolvation was analyzed and contrasted against the combined effect of the first solvation shell in bulk water. Microsolvation reduces the ionization energy (IE) by about 0.1 eV per water molecule, while the first solvation shell increases the IE by 0.1 eV. The subsequent solvation lowers the IE, and the bulk value of the solvent-induced shift of thymine's VIE is approximately -0.9 eV. The combined effect of the first solvation shell was explained in terms of specific solute-solvent interactions, which were investigated using model structures. The convergence of LE to the bulk value requires the hydration sphere of approximately 13.5 angstrom radius. The performance of the EOM-IP-CCSD/EFP scheme was benchmarked against full EOM-IP-CCSD using microhydrated structures. The errors were found to be less than 0.01-0.02 eV. The relative importance of the polarization and higher multipole moments in EFP model was also investigated.